POLA KOMUNIKASI PENYULUH AGAMA ISLAM FUNGSIONAL DALAM PEMBINAAN KEAGAMAAN - Windi Julina (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2020)
Religious guidance will run well, of course, it cannot be separated from the communication pattern built by Islamic religious instructors which combines several communication patterns so that religious development activities become more interesting and effective. The purpose of this study was to describe the communication pattern of functional Islamic religious instructors in the community development of the taklim assembly. This study uses a descriptive research approach. Qualitative research using this descriptive approach provides assistance in understanding the discussions concerning people's lives and the process of inter-community relations. The data used in this study were obtained through data collection techniques, namely observation, interviews and documentation. The steps that researchers use to check the validity of the data in this study are triangulation and member check. The communication process in the religious development of the taklim assembly in conveying a material or message can be said to be good. This is because the material to be delivered has been planned in such a way that it can attract the attention of the communicant.